Successful management of maternal factor VII deficiency in a cesarean section - Lee, Young-Jae (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
Factor VII (FVII) deficiency is an infrequent hereditary bleeding disorder that can make excessive bleeding in surgical interventions, such as a postpartum hemorrhage in a cesarean section. Although a recombinant form of activated FVII has been applied for bleeding control in FVII-deficient patients, its applications in the field of obstetrics are still limited, especially in Korea. Replacement of blood products is still preferred as first-line therapy, with antifibrinolytic agents used as adjunctive therapy. We report herein the case of a successful cesarean section in an 18-year-old woman with FVII deficiency.